A Review on Blockchain for Traceability and Transparency in Sericulture Supply Chains - Harish Reddy C; Mohammad Rafiq Bhat; Sandhya N; Bhuvaneshwar Rajesh Naik; N M Praveen Kumar Gowda (Archives of Current Research International, 2025)
The sericulture industry, despite its cultural and economic importance, remains constrained by fragmented supply chains, limited traceability, and opaque practices that undermine sustainability and authenticity. As global markets increasingly demand verifiable, ethically sourced textiles, blockchain technology emerges as a promising tool for enabling transparency, traceability, and trust. This review explores the role of blockchain and its integration with Internet of Things (IoT), Artificial Intelligence (AI), and smart contracts in transforming the silk supply chain—from mulberry cultivation and silkworm rearing to reeling, dyeing, and retail. Through the documentation of use cases, pilot projects, and policy developments, the paper identifies how blockchain-enabled systems can mitigate fraud, improve farmer livelihoods, ensure quality certification, and support environmentally responsible practices. Real-world implementations in India and China, along with initiatives by global luxury brands, demonstrate its growing relevance. The review also discusses associated challenges, including infrastructure gaps, digital literacy, regulatory constraints, and scalability issues, and proposes mitigation strategies through capacity building, consortium funding, and standardization frameworks. Finally, it outlines future research directions for tailoring blockchain to sericulture-specific needs. Some pilot projects in India and China show the transformational nature of blockchain were observed high price premiums and low payment delay is witnessed. This review links technology frameworks to implementation at grass root level with strategic implications of sustainable digital transformation in the silk sector and offers a roadmap for digitizing silk value chains, positioning blockchain as a foundational technology for sustainable and ethical sericulture.